Towards a socio-ecological system understanding of urban flood risk and barriers to climate change adaptation using causal loop diagrams - Franziska S. Hanf; Felix Ament; Marita Boettcher; Finn Burgemeister; Lidia Gaslikova; Peter Hoffmann; Jörg Knieling; Volker Matthias; Linda Meier; Johannes Pein; Benjamin Poschlod; Markus Quante; et al. (International Journal of Urban Sustainable Development)
While cities are facing increasing challenges of flood risk due to combined effects of climate change and socioeconomic development, understanding of the complexity of urban flood risk is still limited, hampering decision-making and urban adaptation planning. This study presents a qualitative system dynamics modelling framework to investigate urban flood risk and adaptation under climate change in a coupled socio-ecological system, the city of Hamburg. The developed integrated conceptual model provides a holistic understanding of key physical and socio-economic processes and the role of feedback loops underlying the urban system, and contributes to the understanding of vicious cycles of barriers that perpetuate and hinder adaptation processes within cities. The qualitative approach can help to break down silo-thinking in urban flood risk assessments. Decision-makers could use the framework to understand the complexity of interactions among multiple drivers of flood risk to overcome barriers and lock-in effects to adaptation in cities.